ASYMMETRIC IMPACT OF SOME SELECTED MACROECONOMIC VARIABLES ON NATURAL GAS CONSUMPTION IN NIGERIA - SHAMWIL, MUHAMMED; BALA, ABUBAKAR; SHEHU, KAMAL KABIRU; YUNUSA, ABDUL; YARO, IDRISS MOHAMMED (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
This study examined the impact of macroeconomic variables on natural gas consumption in Nigeria during the period 1980–2021 using nonlinear autoregressive distributed lag (NARDL) model. Findings indicated that, natural gas consumption falls with exchange rate appreciation, and rises with depreciation in exchange rate in Nigeria. Also, natural gas consumption falls with increase in inflation rate, and increases with the fall in the rate of inflation. Increase in money supply reduces natural gas consumption, so also decrease in money supply. Finally, the results also revealed that, a rise in economic growth increases natural gas consumption, and as well, a fall in economic growth raises natural gas consumption in Nigeria. The study therefore recommends that, effective use of monetary policy tools in checking the growth of money supply, exchange rate and inflation rate could be of help in boosting natural gas consumption and stirring up economic growth in the country. Since natural gas consumption responds negatively to the changes in the exchange rate, implying that, exchange rate depreciation discourages importation, foreign exchange demand, and propel domestic production which in turn results in more natural gas consumption and improved growth and development in the country.